The Effectiveness of the Digital Environment and Perfectionism on Anxiety and Depression in the Light of the COVID-19 Pandemic in Northern Iraq - Ahmed, Shahla Ali; Cerkez, Yagmur (Frontiers in Psychology, 2022)
This investigation’s intention was to explore the effect of the digital environment as well as perfectionism during the Covid-19 pandemic on anxiety and depression. The study used a mixed methods design; mixed research methodology was used mixed method design regarding explanatory design, using qualitative sub-sample from quantitative sample data. The researcher conducted the study on a sample of 980 student and non-student smartphone and internet users using both qualitative (self-report) and quantitative (questioners) approaches. Three different questionnaires were used: The Multidimensional Perfectionism Scale, Beck Depression Inventory and Beck Anxiety Inventory. On the other hand, the researcher designed a self-report interview for the qualitative part that included 5 major questions and 10 sub-questions. The gathered data was investigated by means of SPSS version 22 to analyse the collected data for this study and simple descriptive statistics and coding were used. The results denote that the digital environment is significantly correlated with multidimensional perfectionism in a low positive manner for students. However, the correlation effects for non-students are significantly high as evidenced by a significant positive correlation. Another finding suggests that there is a positive significant association between perfectionism and being depressed and anxious.